Density and distribution pattern of sea urchin population (diadema setosum) on coral reef (reef flat) At setan island - Steven Silalahi; Syafruddin Nasution; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Density and distribution population of sea urchin Diadema setosum was conducted in May 2014 at Setan Island. The research aimed to know about its density and distribution pattern. The study used survey method by applying transect and plot. The location of research was covering 3 stations. The stations were chosen base on existence of sea urchin D. setosum on coral reef (reef flat). Transect drawn from 5 m up to 15 m depth during low tide. There were there three plots with a size of 3x3 m² along the transect .The results showed that the sea urchin numbers was 332 individuals, where the density range value was 1,367 individuals/m2. The highest density was recorded at station I and the lowest density was found at station III. Morisita indeks dispersion showed that the location had a uniform distribution (Id<1), except for station III had a clumped distribution (Id>1). The highest size frequency of sea urchin D. setosum was ≤2 cm dan the lowest was 4,1-6 cm.Keywords: Setan Island,Density, Distribution,Diadema setosum